História e memória da minha vida e a formação profissional - CARDOSO, Maria Lúcia Pinheiro (2024)
The present work aims to present and analyze my life trajectory, considering the educational practices experienced in my childhood, family experiences, academic formation and teaching, observing the influences of these phases in my pedagogical practices. At last of the events that were remarkable and deserve to be remembered, because they were good or bad. And this work has the purpose of present in a discursive, circumstantial and historical perspective, all this my life trajectory also making an analysis of the academic activities that I developed during the period of formation and in the professional performance. For the development of this memorial was used a research of qualitative approach that has as method the history of life or (auto) biographical method. The results I have achieved here are how the formation process reverted to an awareness of my role as an educator and the changes that this practice causes in my day-to-day with children and at school. Also establishing relations between the theories studied in the pedagogy course and the pedagogical practice in the classroom.